Peningkatan Kemampuan Public Speaking Melalui Layanan Bimbingan Kelompok Teknik Sosiodrama - Berliannisaa, JENNICA (STKIP PGRI SUMENEP, 2025)
The aim of carrying out this research is to describe improving public speaking skills through group guidance services using sociodrama techniques. This research was carried out at Assa'idiyah Kudus Vocational School in the 2023/2024 academic year. The research design uses guidance and counseling action research. The research subjects were ten students of Assa'idiyah Kudus Vocational School. Data collection techniques use observation and interviews. The data analysis used is descriptive quantitative data analysis. The results of the research show that the public speaking skills of Assa'idiyyah Kudus students can be improved through the application of sociodrama technique group guidance. Public speaking ability before providing services is 30% category (Very Poor). In cycle I it was found that there was an increase with a score of 46% in the (Poor) category, then in cycle II there was an increase with a score of 91% in the (Very Good) category.